Assessment of Use of Different Types Of Posts According To The Different Regions Of The Jaw – A Retrospective Study. - MERCHANT, DR.AMAN; MAITI, DR.SUBHABRATA; RAMANATHAN, DR.VISALAKSHI (The journal of contemporary issues in business and government, 2021)
With a variety of options, in terms of materials available for the restoration of the destroyed root structure of endortically treated teeth, for clinical decision of which to use constitutes a challenge to dentist practitioners. The most commonly used posts are prefabricated metal post, prefabricated fibre post and custom made post [cast post]. The purpose of this retrospective study is to check the prevalence of different types of posts and their correlation with age, gender and type of teeth. The correlation is done by the Chi square test. It was found that prefabricated metal posts mostly had the maximum prevalence, followed by prefabricated fibre posts and custom made posts had the least prevalence. Prefabricated posts were more commonly used in female patients, whereas custom made posts were more commonly used in male patients. It was also observed that the maximum number of post treatments were done in young people and the frequency decreased with age. Prefabricated fibre posts and custom made posts were more commonly done in anterior teeth, especially in males, whereas, prefabricated metal posts were more commonly seen in the posterior teeth. More number of studies need to be done to verify the conclusion.